2002
DOI: 10.1063/1.1483626
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature and Strain Rate on the Compressive Behavior of PMMA and Polycarbonate Polymers

Abstract: Abstract. Compression stress-strain measurements have been made on commercial polymethylmethacrylate (PMMA) and polycarbonate (PC) polymers as a function of tcmperature (-197°C to 220°C) and strain rate. A split-Hopkinson-pressure bar (SJIPU) was used to achieve strain rates of about 2500 s-' and a servohydraulic tester was used for lower strain rate testing (0.001 to 5 s-'). The mechanical response of these transparent polymers is quite different. The strength of PC is weakly dependent on strain rate, only m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 2 publications
1
20
0
Order By: Relevance
“…Blumenthal et al measured compressive stress-strain curves of PC [31]; whilst they investigated fewer temperatures and strain rates than this study, data were presented from low strain rate experiments at different temperatures. Their experimental conditions, and the peak stress under each condition, are summarised in Table 2.…”
Section: Compressive Stress-strain Curvesmentioning
confidence: 97%
“…Blumenthal et al measured compressive stress-strain curves of PC [31]; whilst they investigated fewer temperatures and strain rates than this study, data were presented from low strain rate experiments at different temperatures. Their experimental conditions, and the peak stress under each condition, are summarised in Table 2.…”
Section: Compressive Stress-strain Curvesmentioning
confidence: 97%
“…Over the studied temperature range, the yield stress decreased by 67.7%. It is worth mentioning that various researchers found that yield stress, ultimate tensile strength and Young's modulus decreased with increasing temperature [27,30]. The strain at fracture ε fr (characterising an extent of elongation of the specimen elongated to failure) demonstrated different behaviour described with an exponential regression model:…”
Section: Uniaxial Tension Testmentioning
confidence: 98%
“…The first slope gets increasingly milder at higher confining pressures. (Arruda et al, 1995;Blumental et al, 2001;Li and Lambros, 2001;Moy et al, 2003;Van-Melick et al, 1997). Fig.…”
Section: Dynamic Testingmentioning
confidence: 98%